A Study of Several Artificial Viscosity Models within the Discontinuous Galerkin Framework (Communications in Computational Physics, 2020)
Dealing with strong shocks while retaining low numerical dissipation traditionally has been one of the major challenges for high order methods like discontinuous Galerkin (DG). In the literature, shock capturing models have been designed forDG based on various approaches, such as slope limiting, (H)WENO reconstruction, aposteriori sub-cell limiting, and artificial viscosity, among which a subclass of artificial viscosity methods are compared in the present work. Four models are evaluated,including a dilation-based model, a highest modal decay model, an averaged modaldecay model, and an entropy viscosity model. Performance for smooth, non-smoothand broadband problems are examined with typical one- and two-dimensional cases.
Keywords: High order methods; discontinuous Galerkin; shock capturing; artificial viscosity.